Fashion, Sustainability, and Tourism: How Soerakarta Walking Tour Engages Muslim Community in Green Tourism - Mumpuni, Restu Ayu; Nurpratiwi, Hany; Rusdini, Siti Ekowati; Sinaga, Syahrul Syah (Forum Ilmu Sosial, 2025)
The Soerakarta Walking Tour (SWT) is an innovative urban tourism initiative that integrates cultural preservation, environmental sustainability, and inclusivity. This study examines how SWT's promotes green tourism through a mixed-methods approach, combining quantitative surveys and qualitative interviews with participants. The quantitative findings reveal high levels of participant satisfaction, including understanding green tourism principles and satisfaction with cultural storytelling. Qualitative data complement these results, highlighting participants’ appreciation for Muslim-friendly facilities, opportunities for cultural learning, and the promotion of local economic and environmental sustainability. The study applies the frameworks of Integrated Marketing Communication (IMC) and Social Marketing to analyze how SWT delivers consistent and engaging messages while fostering behavioral change. The findings show that SWT successfully inspires participants to adopt sustainable practices, though some variability in the visibility of green tourism principles suggests room for improvement.